Turnover intention and job satisfaction among nurses in a tertiary level hospital (Journal of Patan Academy of Health Sciences, 2024)
Introduction: Turnover intention, the likelihood of leaving a job, is a global challenge in nursing, affecting healthcare stability. Job satisfaction, a positive attitude toward job stability and professional growth, plays a crucial role in retaining nurses and ensuring quality care.This study aims to identify turnover intention and job satisfaction level among nurses.Method: A mixed-method descriptive cross-sectional study design with a simple random sampling technique, select 422 nurses from a tertiary-level hospital in Lalitpur, Nepal. Data were collected from 408 nurses using the Job Satisfaction Survey (JSS) and Turnover Intention Scale (TIS-6) from January to March 2024. Data were analyzed using SPSS 16 for quantitative data, descriptive statistics for socio-demographics, job satisfaction, and turnover intention levels. A chi-square test examined the association between turnover intention and job satisfaction. Thematic analysis was done for open-ended questions.Result: More than half, 243(59.6%), reported ambivalence, 123(30.10%) were satisfied, and 42(10.30%) were dissatisfied with their jobs. Additionally, 205(50.20%) reported turnover intention, while 203(49.8%) did not. There was a significant association between turnover intention and job satisfaction among nurses in the tertiary-level hospital (p